Food Security and Nutritional Status of Children in Fishing Community - Addy, P.S. (University of Ghana, 1999)
This study was done to ascertain the food security and nutritional status of children aged between two and five years in Kpone, a fishing community in the Greater Accra region of Ghana. The objectives were to assess (i) some household and child health characteristics, (ii) dietary adequacy for energy, protein, iron and vitamin A, (iii) the food security status of the children, (iv) growth by anthropometry and (v) serum iron and vitamin A status of the children. In the major fish season, 336 children were involved in the study while the number reduced to 274 due to attrition in the lean fish season. Results of the study showed that, 12% of the children had malaria, 6% coughs and 5% measles. The immunization status was encouraging as 73% had completed all vaccinations against the childhood killer diseases. Sanitation was rather poor with 74% of the households found to be in poor living conditions. Diarrhoea prevalence was very high with as many as 70% of the children having very severe diarrhoea. For energy intake, as many as 60% could not meet their recommended dietary allowance (RDA) in the lean fish season but there was an improvement in the major season as this level reduced to 51%. Protein requirements were met by 87% of the children in both seasons while iron needs were satisfied by 40% and 57% of the children in the lean and major fish seasons respectively. Vitamin A needs, were met by 58% of the children in both lean and major fish seasons. There were no significant diffemces in the mean intakes for energy, protein and vitamin A for the two seasons but there was a significant difference in the mean intake for iron (p < 0.001). Using the Dietary Energy Adequacy Ratio (DEAR) of 0.8 for food security status, 68% of the children could be classified as food insecure in the lean fish season while in the major fish season, the level reduced to 59%. With growth determination using anthropometry, prevalence of stunting (both moderate and severe) was 49% at baseline. Prevalence of underweight was 46% in the lean season, dropping to 29% in the major fish season. Wasting prevalence increased from 5% to 8%. The results show that about a third of the children are not getting enough to eat and and this has translated into poor growth, hence the rather high prevalence of undemutrition shown by anthropometry. The prevalence of iron deficiency in the form of prelatent iron status showed that as 75% of the children had serum ferritin levels below 50 Hg/1, representing a vulnerable state. In the case of vitamin A status using retionol binding protein, 12% of the children had serum retinol binding protein levels below the lower cut off point of 18jag/l. Children in this community are at risk of poor nutrition and the community at large can be mapped as one vulnerable to food insecurity.
Thesis (MPhil)-University of Ghana